Marine Biodiversity 2006
DOI: 10.1007/1-4020-4697-9_1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between phytoplankton diversity and community function in a coastal lagoon

Abstract: The decrease of biodiversity related to the phenomena of global climate change is stimulating the scientific community towards a better understanding of the relationships between biodiversity and ecosystem functioning. In ecosystems where marked biodiversity changes occur at seasonal time scales, it is easier to relate them with ecosystem functioning. The objective of this work is to analyse the relationship between phytoplankton diversity and primary production in St. Andre´coastal lagoon -SW Portugal. This l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
4
22
0
1
Order By: Relevance
“…The annual dynamics of water renewal in Santo André lagoon and the inherent year-to-year variability of physical conditions in lagoons (Barnes, 1980;Desmond et al, 2002) lead to a high temporal variability in biological communities (phytoplankton community e Duarte et al, 2006; Ruppia cirrhosa e Calado and Duarte, 2000; benthic community, as it was found in this study). Benthic community sampled in the present study consisted of 42 taxa, most of which are typical of these lagoonal systems (e.g.…”
Section: Discussionsupporting
confidence: 69%
“…The annual dynamics of water renewal in Santo André lagoon and the inherent year-to-year variability of physical conditions in lagoons (Barnes, 1980;Desmond et al, 2002) lead to a high temporal variability in biological communities (phytoplankton community e Duarte et al, 2006; Ruppia cirrhosa e Calado and Duarte, 2000; benthic community, as it was found in this study). Benthic community sampled in the present study consisted of 42 taxa, most of which are typical of these lagoonal systems (e.g.…”
Section: Discussionsupporting
confidence: 69%
“…The range in modeled SI compares to that reported by Irigoien et al (2004) but not to the high cytometric diversity values of Li (2002), which upon conversion of the exponential form reach high diversity values of 4.3 due to the representation of both physiological and genetic variation among organisms rather than solely taxonomy. Similar to the observed scatter reported by most observations in non-marine (Adler et al, 2011) and marine (Li, 2002;Irigoien et al, 2004;Duarte et al, 2006) systems, the scatter in our model results does not reveal a straightforward curvilinear relationship between diversity and productivity, consistent with Adler et al's (2011) argument that many factors contribute to the variation in diversity and therefore diversity-productivity relationships.…”
Section: The Diversity-productivity Scattersupporting
confidence: 91%
“…Studies of pelagic aquatic environments have also documented unimodallike structure, though usually with considerable scatter similar to that conceptualized in Fig. 1d (Agard et al, 1996;Li, 2002;Grover and Chrzanowski, 2004;Irigoien et al, 2004;Duarte et al, 2006;Spatharis et al, 2008). Cermeno et al (2008) find no statistical relationship in their analysis of coastal, shelf, and open ocean environments.…”
Section: Introductionmentioning
confidence: 93%
“…In marine ecosystems, there seems to be a general decreasing trend of the P/B ratio as a function of net primary production (NPP). In one extreme there are oligotrophic ecosystems, with high P/B, low biomass and NPP, such as open ocean pelagic systems, and in another extreme there are ecosystems with low P/B, high NPP and biomass, such as algal reefs and beds (Duarte et al, 2006). These trends suggest that low biomass and NPP ecosystems are more efficient in using limiting resources.…”
Section: Discussionmentioning
confidence: 99%